PLAY STUDY: EDUCATIONAL GAME SEBAGAI MEDIA BELAJARPENDIDIKAN SEKS BAGI ANAK SEKOLAH DASAR - Adhy Putri Rilianti dan Amalia Ima (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
The research was aimed at designing and producing an educative game called Play Study as alearning media in sex education for elementary school students, and revealing its validity andeffectiveness.The research method used was Research and Development. The steps were (1) need analysis, (2)model design, (3) implementation, and (4) test. The research was conducted in Sambiroto,Purwomartani, Kalasan District, Sleman Regency, Yogyakarta.The result of testing the Educative Game “Play Study” by using alpha testing through questionnaireanalysis by a media expert showed that this game was feasible to use after being revised. In the betatesting it was shown that children could use the game well so their understanding of sex educationimproved.Key words: Play Study, learning media, sex education for children